Leadership, leaders and leading - Sims, Ronald R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Why with hundreds and hundreds of books on leadership to choose from, why another one?" The answer is simple. Given the importance of leadership and leaders in organizations there will always be efforts to try to improve our understanding on how we can improve the leadership process. Leadership, leaders and leading focuses on the age old reality that successful organizations will continue to need effective leaders at all levels. The book is based on the premise that effective leaders need to be able to establish a shared vision and accompanying strategy that other members of the organization strongly believe in and are willing to help execute. The book argues that we can continue to learn from traditional and contemporary theories and myths about effective leadership & leaders and how they can successfully lead an increasingly diverse and demanding workforce, consumers and the broader society. The book discusses foundational leadership skills like motivation, communication, building leader-follower relationships, groups and teams, developing others, conflict, negotiation and organizational politics along with highlighting the important role leaders should play in the areas of human resource management, ethics, crisis and reputation management, sustainability/sustainable development, and cybersecurity. Each chapter offers the opportunity for the reader to increase their understanding of leadership, leaders and leading in an increasingly dynamic world of work. This book is written for those who are interested in the continued effort and dialogue on what effective leadership, leaders and leading should entail in the coming years"-- Provided by publisher.
Keywords: Personnel management.; Communication in management.; Industrial management.; Employees -- Training of.; Conflict management.; Computer networks -- Security measures.; Organizational change.; Leadership.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books